The Effects of the Anti-aging Protein Klotho on Mucociliary Clearance - Garth, Jaleesa; Easter, Molly; Skylar Harris, Elex; Sailland, Juliette; Kuenzi, Lisa; Chung, Samuel; Dennis, John S.; Baumlin, Nathalie; Adewale, Adegboyega T.; Rowe, Steven M.; King, Gwendalyn; Faul, Christian; et al. (Frontiers in Medicine, 2020)
Alpha-klotho (KL) is an anti-aging protein and has been shown to exert anti-inflammatory and anti-oxidative effects in the lung and pulmonary diseases such as chronic obstructive pulmonary disease (COPD) and cystic fibrosis. The current study investigated the direct effect of KL on the bronchial epithelium in regards to mucociliary clearance parameters. Primary human bronchial and murine tracheal epithelial cells, cultured and differentiated at the air liquid interface (ALI), were treated with recombinant KL or infected with a lentiviral vector expressing KL. Airway surface liquid (ASL) volume, airway ion channel activities and expression levels were analyzed. These experiments were paired with ex vivo analyses of mucociliary clearance in murine tracheas from klotho deficient mice and their wild type littermates. Our results showed that klotho deficiency led to impaired mucociliary clearance with a reduction in ASL volume in vitro and ex vivo. Overexpression or exogenous KL increased ASL volume, which was paralleled by increased activation of the large-conductance, Ca2+-activated, voltage-dependent potassium channel (BK) without effect on the cystic fibrosis transmembrane conductance regulator (CFTR). Furthermore, KL overexpression downregulated IL-8 levels and attenuated TGF-beta-mediated downregulation of LRRC26, the  subunit of BK, necessary for its function in non-excitable cells. In summary, we show that KL regulates mucociliary function by increasing ASL volume in the airways possibly due to underlying BK activation. The KL mediated BK channel activation may be a potentially important target to design therapeutic strategies in inflammatory airway diseases when ASL volume is decreased.